201k views
4 votes
Which expression is equal to (f - g)(x)?

Which expression is equal to (f - g)(x)?-example-1

2 Answers

3 votes

Answer:

11|x|-32 hope this helps :D

Explanation:

10|x|+26-(58-|x|)

10|x|+26-58+|x|

10|x|+|x|+26-58

11|x|-32

User Ramin Afshar
by
4.9k points
4 votes

ANSWER


(f-g)(x) = 11 |x| - 32

EXPLANATION

The functions are:


f(x) = 10 |x| + 26


g(x) = 58 - |x|


(f-g)(x) = f(x) - g(x)

Plug in the functions:


(f-g)(x) = 10 |x| + 26 - (58 - |x| )


(f-g)(x) = 10 |x| + 26 - 58 + |x|


(f-g)(x) = 10 |x| + |x| + 26 - 58


(f-g)(x) = 11 |x| - 32

The correct choice is A

User Teysz
by
5.1k points